Disrupting the International Student Recruitment Middleman: From Agents to Algorithms - Nikula, Pii-Tuulia (International Higher Education, 2025)
<h3 id="the-debate-surrounding-the-ethical-dilemmas-associated-with-education-agents-has-persisted-for-decades-at-the-same-time-the-use-of-agents-has-grown-rapidly-suggesting-that-many-higher-education-institutions-and-prospective-international-students-continue-to-perceive-value-in-their-services-this-article-examines-the-key-drivers-behind-agent-engagement-explores-the-ethical-concerns-it-raises-and-considers-how-generative-artificial-intelligence-may-reshape-the-future-of-international-student-recruitment" data-pm-slice="1 1 []">The debate surrounding the ethical dilemmas associated with education agents has persisted for decades. At the same time, the use of agents has grown rapidly, suggesting that many higher education institutions and prospective international students continue to perceive value in their services. This article examines the key drivers behind agent engagement, explores the ethical concerns it raises, and considers how generative artificial intelligence may reshape the future of international student recruitment.